2020
DOI: 10.1136/jech-2019-213068
|View full text |Cite
|
Sign up to set email alerts
|

Older LGBT+ health inequalities in the UK: setting a research agenda

Abstract: Lesbian, gay, bisexual and trans+ a (LGBT+) people report poorer health than the general population and worse experiences of healthcare particularly cancer, palliative/end-of-life, dementia and mental health provision. This is attributable to: a) social inequalities, including 'minority stress'; b) associated health-risk behaviours (e.g. smoking, excessive drug/alcohol use, obesity); c) loneliness and isolation, affecting physical/mental health and mortality; d) anticipated/experienced discrimination and e) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 26 publications
2
65
0
2
Order By: Relevance
“…However, where evidence does exist, this overwhelmingly suggests that higher levels of pre-existing health conditions compared to cisgender and heterosexual populations, may place the LGBTQ+ community at additional risk of adverse prognosis. This includes long-term chronic illness, and higher rates of smoking and asthma among LGBTQ+ people [2][3][4][5][6][7][8]; higher rates of obesity, and alcohol consumption among lesbian, bisexual, and queer women [7 9 10]; and increased likelihood of being immunocompromised (e.g. HIV+ with a low CD4 cell count or with untreated HIV) among gay men and transgender people [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, where evidence does exist, this overwhelmingly suggests that higher levels of pre-existing health conditions compared to cisgender and heterosexual populations, may place the LGBTQ+ community at additional risk of adverse prognosis. This includes long-term chronic illness, and higher rates of smoking and asthma among LGBTQ+ people [2][3][4][5][6][7][8]; higher rates of obesity, and alcohol consumption among lesbian, bisexual, and queer women [7 9 10]; and increased likelihood of being immunocompromised (e.g. HIV+ with a low CD4 cell count or with untreated HIV) among gay men and transgender people [11].…”
Section: Introductionmentioning
confidence: 99%
“…The public health case for disclosure of LGBT status in healthcare, in contrast, rests primarily on population-level benefits to disclosure: that collecting data on the whole LGBT population could improve the capabilities of LGBT people to achieve good health, for example through better understandings of risk, and targeting of interventions [ 5 ]. These collective capabilities are most enhanced if all LGBT people disclose their status.…”
Section: Discussionmentioning
confidence: 99%
“…However sexual orientation and gender identity are often not consistently recorded in key datasets such as censuses, patient records and mortality registries. This has resulted in a lack of large-scale data on key later-life morbidity and mortality outcomes in LGBT populations, such as cardiovascular disease, diabetes, cancer and other long-term conditions and conditions of ageing [ 5 , 6 , 7 , 8 ]. There are a number of social and practical factors that may underpin this historic lack of data collection, including the small, dispersed nature of the population; the history of criminalisation and pathologisation; concerns about sensitivity and privacy; uncertainty over when and how to record data; and a perception that LGBT populations have few or no distinct health needs [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers and health organisations have shown that health research disparities exist between lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ+) populations and heterosexual people. 1 , 2 , 3 Such research gaps have contributed to a health knowledge deficit for LGBTQ+ populations and resulted in few evidence-based interventions that address the many health inequities that disproportionately affect these populations across the lifespan. 1 Evidence points to LGBTQ+ populations having greater rates of chronic disease (eg, diabetes, coronary heart disease, and certain forms of cancer), social health problems (eg, violence, discrimination, exclusion, and loneliness), and mental health symptoms and disorders (eg, depression, anxiety, substance use, and suicide).…”
mentioning
confidence: 99%
“…1 Evidence points to LGBTQ+ populations having greater rates of chronic disease (eg, diabetes, coronary heart disease, and certain forms of cancer), social health problems (eg, violence, discrimination, exclusion, and loneliness), and mental health symptoms and disorders (eg, depression, anxiety, substance use, and suicide). 1 , 2 , 3 , 4 Despite calls for the inclusion of sexual and gender identity being collected as part of demographic information in health research and the creation of LGBTQ+ focused health interventions, 1 , 2 , 3 such calls have not been fully addressed.…”
mentioning
confidence: 99%